Molecular pathophysiology of human MICU1 deficiency. (22nd February 2021) - Kohlschmidt, Nicolai; Elbracht, Miriam; Czech, Artur; Häusler, Martin; Phan, Vietxuan; Töpf, Ana; Huang, Kai‐Ting; Bartok, Adam; Eggermann, Katja; Zippel, Stephanie; Eggermann, Thomas; Freier, Erik; et al.
Abstract: Aims: MICU1 encodes the gatekeeper of the mitochondrial Ca 2+ uniporter, MICU1 and biallelic loss‐of‐function mutations cause a complex, neuromuscular disorder in children. Although the role of the protein is well understood, the precise molecular pathophysiology leading to this neuropaediatric phenotype has not been fully elucidated. Here we aimed to obtain novel insights into MICU1 pathophysiology. Methods: Molecular genetic studies along with proteomic profiling, electron‐, light‐ and Coherent anti‐Stokes Raman scattering microscopy and immuno‐based studies of protein abundances and Ca 2+ transport studies were employed to examine the pathophysiology of MICU1 deficiency in humans. Results: We describe two patients carrying MICU1 mutations, two nonsense (c.52C>T; p.(Arg18*) and c.553C>T; p.(Arg185*)) and an intragenic exon 2‐deletion presenting with ataxia, developmental delay and early onset myopathy, clinodactyly, attention deficits, insomnia and impaired cognitive pain perception. Muscle biopsies revealed signs of dystrophy and neurogenic atrophy, severe mitochondrial perturbations, altered Golgi structure, vacuoles and altered lipid homeostasis. Comparative mitochondrial Ca 2+ transport and proteomic studies on lymphoblastoid cells revealed that the [Ca 2+ ] threshold and the cooperative activation of mitochondrial Ca 2+ uptake were lost in MICU1‐deficient cells and that 39 proteins were altered in abundance. Several of those proteins are linked to mitochondrial dysfunction and/or perturbed Ca 2+ homeostasis, also impacting on regular cytoskeleton (affecting Spectrin) and Golgi architecture, as well as cellular survival mechanisms. Conclusions: Our findings (i) link dysregulation of mitochondrial Ca 2+ uptake with muscle pathology (including perturbed lipid homeostasis and ER–Golgi morphology), (ii) support the concept of a functional interplay of ER–Golgi and mitochondria in lipid homeostasis and (iii) reveal the vulnerability of the cellular proteome as part of the MICU1‐related pathophysiology. Abstract : Applied research strategy toward the identification of pathomechanisms upon human MICU1‐deficiency includes (i) phenotyping of the patient, (ii) molecular genetic investigations, (iii) biochemical characterization of patient‐derived lymphoblastoid cells including proteomics and Calcium release studies as well as (iv) precise characterization of muscle biopsy specimen including histology, electron and Coherent Anti‐Stokes Raman Scattering microscopy and immunostaining studies.